PECULIARITIES OF MIXING METALS IN INTERGALACTIC AND INTERSTELLAR MEDIA - Dedikov, S. Yu.; Shchekinov, Yu. A.; Vasiliev, E. O. (Одеські астрономічні публікації, 2008)
We review the current status of the problem of metal mixing in the intergalactic and interstellar media. We give simple arguments for inefficiency of mixing metals because of a saturation of hydrodynamic (Rayleigh-Taylor and Kelvin-Helmholz) instabilities. We describe mixing in two typical processes: stripping of a galactic gaseous halo and cloud-cloud collision. We show that statistical features of metal distribution observed in the intergalactic medium is close to those obtained in our numerical simulations.